Research Status and Prospect of Laser Scribing Process and Equipment for Chemical Milling Parts in Aviation and Aerospace - Jian Wang; Qiang Liu; Pengpeng Sun; Chenxin Zang; Liuquan Wang; Zhiwei Ning; Ming Li; Hui Wang (Micromachines, 2022)
Laser scribing in chemical milling is an important process which can effectively improve the precision and efficiency of chemical milling, and is of great significance to improve the thrust–weight ratio and manufacturing efficiency of aviation and aerospace parts. According to the scribing requirements in chemical milling for aviation and aerospace parts, the process and mechanism of laser scribing were studied and the influence of different process parameters for the quality of laser scribing was analyzed. Based on the review of related research literature, the laser scribing process, the ablation mechanism and technology of different materials and the selective laser removal process for “laser–coating–substrate” are summarized and discussed. Based on the requirements of high-precision laser scribing on complex surfaces, the current situation of laser scribing equipment is summarized. Finally, the practical challenges and key technical problems for the laser scribing process are summarized, and the application and development of laser scribing in aerospace manufacturing are prospected.